SFRP1 inhibited the epithelial ovarian cancer through inhibiting Wnt/β-catenin signaling - Zhang, Hao; Sun, Duohe; Qiu, Jianping; Yao, Liangqing (Acta biochimica Polonica, 2019)
Background: Epithelial ovarian cancer is the most malignant gynecologic neoplasm accounting for 90% of the ovarian cancer patients. Objective: Researchers proved that epigenetic alterations could disrupt gene expression as often as genetic alterations. Secreted frizzed related protein (SFRP1), a Wnt antagonist, exerts a significant effect on ovarian cancer. The aim of this research was to investigate the effects and the mechanism of action of SFRP1 on epithelial ovarian cancer. Methods: Clinical specimens (including fallopian tubes epithelium from 60 epithelial ovarian cancer patients’ and 20 healthy subjects who were undergoing surgical treatments), transgenic mice (overexpressing SFRP1 gene), and 4 epithelial ovarian cancer cell lines (including OVCAR4, SKOV3, COV644, TOV21G) were used in this study. Overexpression of SFRP1 in cells was carried out on OVCAR4 cells by transfection using Lipofectamine 2000. Gene transcription was analyzed by qRT-PCR. The methylation of SFRP1 gene was quantified by methylation-specific PCR. The level of protein expression was measured by Western blot or immunohistochemistry analysis. Cell proliferation was analyzed by CCK8 methods. The ability of cell migration and invasion were measured by wound healing assay and transwell assay. Results: Abnormal expression level and hypermethylation status of SFRP1 were found in clinical epithelial ovarian cancer samples and cell lines. We observed that SFRP1 knockdown could promote proliferation, migration and invasion abilities of epithelial ovarian cancer cells. Additionally, we discovered a potential inhibitory effect of SFRP1 on Wnt/β-catenin signaling pathway in epithelial ovarian cancer cells. Furthermore, the anti-tumor effect of SFRP1 was tested in SFRP1 transgenic mice. Conclusion: SFRP1 inhibited epithelial ovarian cancer through inhibiting Wnt/β-catenin pathway, suggesting that SFRP1 could be considered as a potential therapeutic target in epithelial ovarian cancer.